SEMANTIC SHIFTS AND CALQUING: HOW SUBCULTURE TERMS RESHAPE UZBEK LANGUAGE NORMS - Ergasheva, Nigora (Mental Enlightenment Scientific-Methodological Journal, 2025)
This article examines the impact of subculture terminology on the semantic evolution of the Uzbek language, focusing on lexical borrowing and calquing as key mechanisms of change. Bringing about theoretical frameworks from Michael Cronin’s Translation and Globalization (2003) and David Katan’s Translating Cultures (1999), this paper explores how subcultural expressions – specifically from youth, internet, and urban subcultures – are integrated into Uzbek, leading to semantic shifts and hybrid lexical formations. Data is drawn from social media, music lyrics, and interviews with Uzbek speakers. The finding suggest that these processes reflect broader sociolinguistic trends related to globalization and cultural exchange; while English and Russian dominate as source languages, Uzbek language’s agglutinative structure facilitates creative, reshaping normative usage among younger generation.